2021
DOI: 10.3390/ijerph182111525
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological and Behavioral Patterns of Online Psychological Help-Seekers before and during COVID-19 Pandemic: A Text Mining-Based Longitudinal Ecological Study

Abstract: Online mental health service (OMHS) platforms have contributed significantly to the public’s mental health during the COVID-19 pandemic in China. However, it remains unclear why the public used OMHS platforms for psychological help-seeking (PHS) behavior and how PHS behavior varied across different stages of the COVID-19 pandemic. Based on the ecological PHS behavior data from two OMHS platforms, we extracted population, psychological problems, and influential factors of PHS behavior by text mining and time se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…A previous study points out that there is an explosive increase in OPHS after the outbreak of the COVID-19, and the OPHS number varies across different stages during the pandemic ( 62 ). From the perspective of taking immediate crisis response, the use of machine learning techniques may provide more accurate predicted values of OPHS behavior, which enables governments and OMHS platforms to rationally organize and allocate valuable counselors based on the help-seeking trends.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study points out that there is an explosive increase in OPHS after the outbreak of the COVID-19, and the OPHS number varies across different stages during the pandemic ( 62 ). From the perspective of taking immediate crisis response, the use of machine learning techniques may provide more accurate predicted values of OPHS behavior, which enables governments and OMHS platforms to rationally organize and allocate valuable counselors based on the help-seeking trends.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors found that female gender, older age, and more severe anxiety, as well as depressive symptoms, were associated with stronger emotions of fear regarding COVID-19. 37 Huang et al 38 disclosed that the public’s negative affect during the COVID-19 pandemic in China rose sharply after the declaration of the COVID-19 outbreak. The authors identified seven psychological disturbances: “depression and anxiety, lack of interest, suicidal tendencies, social phobia, feelings of being worried and afraid, suffering, and anger.” 38…”
Section: Discussionmentioning
confidence: 99%
“…37 Huang et al 38 disclosed that the public’s negative affect during the COVID-19 pandemic in China rose sharply after the declaration of the COVID-19 outbreak. The authors identified seven psychological disturbances: “depression and anxiety, lack of interest, suicidal tendencies, social phobia, feelings of being worried and afraid, suffering, and anger.” 38…”
Section: Discussionmentioning
confidence: 99%
“…According to former researchers which applied word embedding to identifying psychological topics in online psychological help seeking texts ( 9 , 48 ), we proposed following four steps. Firstly, a predefined lexicon regarding psychological symptoms and influential linguistic cues of was constructed.…”
Section: Data Methods and Measuresmentioning
confidence: 99%
“…Online counseling encompasses a wide range of techniques, including but not limited to instant messaging, synchronous chat, text messaging, video conferencing, and asynchronous email (7). There has been evidence showing that the break out of COVID-19 has boosted the use of online counseling worldwide (7)(8)(9). Still, access to mental health care remains a global challenge with widespread shortages of the workforce (10).…”
Section: Introductionmentioning
confidence: 99%